2019
DOI: 10.1016/j.joule.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

An Equivalent Circuit for Perovskite Solar Cell Bridging Sensitized to Thin Film Architectures

Abstract: The control over the precursor concentration is used to fabricate sensitized and thin-film perovskite solar cells. The dominating capacitance contributions in these devices reveal the main processes determining the response of perovskite solar cells, which enables the development of an impedance spectroscopy equivalent circuit for perovskite solar cells derived from the well-known circuit for sensitized devices. This tool can provide essential information for the photovoltaic performance in terms of transport … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 62 publications
(140 reference statements)
7
108
2
Order By: Relevance
“…In this case, R rec can be simply obtained by the sum of R HF and R LF . [ 60 ] As shown in Figure 4C, the diameters of the two arcs for NMAI‐treated sample (fitted with red line) are larger than those of the control sample (fitted with black line). It means that the devices with the NMAI treatment have larger R rec which is related to the reduced surface/interface trap states and other recombination centers.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this case, R rec can be simply obtained by the sum of R HF and R LF . [ 60 ] As shown in Figure 4C, the diameters of the two arcs for NMAI‐treated sample (fitted with red line) are larger than those of the control sample (fitted with black line). It means that the devices with the NMAI treatment have larger R rec which is related to the reduced surface/interface trap states and other recombination centers.…”
Section: Resultsmentioning
confidence: 96%
“…The charge dynamic behavior in the complete device is further investigated via electrochemical impedance spectroscopy (EIS), transient photovoltage decay (TPV) and space‐charge‐limited current (SCLC) measurements on both types of samples. The EIS data measured at a bias of 0.75 V under 1 sun illumination was fitted to two arcs at high frequencies (HF) and low frequencies (LF), respectively, using an equivalent circuit model proposed by Mora‐Seró [ 60 ] (Figure 4C inset) Given the fact that the transport resistance ( R t ) is much smaller than recombination resistance ( R rec ) in the high‐performance PSCs, R t can be neglected in the equivalent circuit. In this case, R rec can be simply obtained by the sum of R HF and R LF .…”
Section: Resultsmentioning
confidence: 99%
“…The Nyquist plots were obtained in the dark with an applied bias voltage of 1.0 V and the fitted parameters are summarized in Table S4, Supporting Information. As shown in the equivalent circuit, the internal series resistance ( R s ) was related to the sheet resistance of the electrodes and the charge‐transfer resistance ( R ct ), corresponding to the semicircle in the high frequency region 46,47. The R s values of the three PSCs was similarly.…”
Section: Photovoltaic Performance Of Champion Pscs Based On Differentmentioning
confidence: 96%
“…Measurements were carried out under Xenon lamp (intensity 100 mW cm −2 ) illumination over a wide range of applied voltages and frequencies (from 0 up to V oc and from 1 MHz to 0.1 Hz) . The fitting has been performed using the equivalent circuits discussed by Yoo et al and the recombination resistance ( R rec ) has been approached by addition of the resistances of high frequency and low frequency (lf) semicircles obtained in the Nyquist plot, (Figure S5, Supporting Information). From IS analysis, it was observed that the R rec of the average UVO 60 min SnO 2 ‐treated PSC is significantly higher than that of UVO 0 min SnO 2 PSC over nearly the entire range of the studied voltage bias, indicating that the non‐radiative recombination rate is significantly lower (Figure b).…”
Section: Figures Of Merits Jsc Ff Voc and Pce Expressed As Mean mentioning
confidence: 99%